因併購交易簽訂的禁止聘僱條款是否合法？從臺灣競爭法角度觀之 Should No-Poaching Agreements Be Prohibited in Corporate Transactions? From the View of Taiwanese Competition Law - 鄭歆儒 Shin-Ru Cheng (交大法學評論)
在併購交易的協商過程中，雙方或簽訂禁止聘僱條款，限制一方於交易過程進行中（或結束後）聘僱他方之員工。該條款固能防止因併購交易發生的惡意招募行為，但也嚴重限制員工到他方公司任職的轉職自由，使員工與現在雇主在薪資福利的協商上陷於談判劣勢。有鑑於現有勞動法規似未能有效規範此問題，本文嘗試從競爭法角度探討該條款的合法性。透過比較分析外國及臺灣的競爭法及相關案例，本文釐清禁止聘僱條款的相關市場範圍、限制競爭與促進競爭效果。本文主張為保障弱勢的勞工族群，該條款須為保障併購交易雙方利益且損害最小的方法時，方能認為該條款的促進競爭效果優於限制競爭效果。在盡職調查過程中委由獨立團隊閱覽員工資訊，不須限制勞工的轉職自由即能避免經營團隊利用該等資訊惡意聘僱他方員工，與禁 止聘僱條款相較應屬損害更小的方法。因此除非個案中組成獨立團隊有其困難，應認禁止聘僱條款違反競爭法。 No-poaching agreements (NPAs) prohibit parties from recruiting each other’s employees. While the agreements can prevent unethical recruitment in corporate transactions, they reduce external job options for laborers, thereby significantly harming their bargaining power. Yet, employment law and labor law appear to face difficulties of addressing the problem. This article seeks to tackle the problem by examining the legality of NPAs under Taiwanese competition law. With reference to the major jurisdictions and Taiwan’s competition law and previous cases, this article clarifies the relevant market of NPAs and their anticompetitive harms and procompetitive benefits. It argues that NPAs should be prohibited under competition law, even to protect parties’ interests in corporate transactions, because organizing an independent team to manage employee information is a less restrictive way to achieve the same goal.